Pengaruh E-Service Quality Terhadap E-Satisfaction Yang Dimediasi Oleh E-Trust Pada Aplikasi Starbucks ID di Indonesia - Asni Arini Solehah; Arif Kuswanto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The development of the digital era facilitates activities and work in various fields due to the presence of internet networks, social media, digital devices, and digital platforms. One business that is starting to use technology is the coffee shop business. More and more venture capital companies are injecting capital into coffee shops. The existence of these investors makes the speed of the cafe business faster. One of them begins by implementing computerized innovation in its operations (Adventa, 2019).Starbucks Corporation is an American coffee company and a worldwide network of cafes located in Seattle, Washington. Starbucks launched an application that can be downloaded from the application store or playstore. But there are still some bad reviews from users. One of them is the problem when users will top up. The purpose of this study is to determine the effect of e-service quality on e-satisfaction mediated by e-trust in the starbucks id application in Indonesia. This research genre is quantitative with descriptive analysis. The number of respondents in this study were 385 respondents distributed to Starbucks ID application users in Indonesia. The result is that e-service quality has a positive and significant effect on e-satisfaction. E-service quality has a positive and significant effect on e-trust. E-trust has a positive and significant effect on e-satisfaction. And e-service quality has a positive and significant effect on e-satisfaction mediated by e-trust.